Effect of Different Concentration of Seaweed Saps on Quality, Green Fodder and Seed Yields of Berseem (Trifolium alexandrium) - Jha, A. K.; Shrivastava, Arti; Mehta, A. K.; Billaiya, S. K.; Raghuvanshi, N. S. (International Journal of Bio-resource and Stress Management, 2016)
A field experiment was conducted during rabi seasons 2012 and 2013 at research farm of Department of Agronomy Jawaharlal Nehru Krishi Vishwa-Vidyalaya, Jabalpur, Madhya Pradesh, India. The experiment was laid out in Randomized Block Design in three replications with ten treatments are as follows: RDF+2.5% K-sap, RDF+5% K sap, RDF+7.5% K sap, RDF+10% K sap, RDF+2.5% G sap, RDF+5% G sap, RDF+7.5% G sap, RDF+10% G sap, RDF+water spray, 50% RDF+6.25% K sap. The sowing date of Berseem variety- JB-5 were sown on 17th November, 2012 and 19th November of 2013. The highest GFY and DMY were recorded with the application of RDF with 10% G sap (613.45 and 83.24 q ha-1) followed by application of RDF+10% K sap (607.35 and 82.01 q ha-1), similarly the maximum seed yield and stover yield were recorded with the application of RDF with 10% G sap (4.72 and 62.36 q ha-1) followed by application of RDF+10% K sap (4.07 and 60.59 q ha-1), respectively due to presence of growth promoting hormones (Auxins, Cytokinins, Gibberellins), trace elements, vitamins, amino acids, antibiotics and micronutrients in these saps. The higher crude protein yield and crude fiber yield were observed under application of 10% G sap+RDF (11.67 and 15.10 q ha-1) followed by10% K sap+RDF (11.83 and 15.34 q ha-1).